Влияние гусеницы на динамику транспортной машины - Александров, Евгений Евгеньевич; Пидашов, В. В. (НТУ "ХПИ", 2007)
The influence of a variable track tension on dynamic of the high-speed transport track vehicle during its motion on crossed districts is considered. The sequence of calculation of a tension on different sites of full-track bypass is reduced.
Keywords: переменное натягивание; расчет натягивания